2010
DOI: 10.1051/vetres/2010016
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathic bovine viral diarrhea viruses (BVDV): emerging pestiviruses doomed to extinction

Abstract: Bovine viral diarrhea virus (BVDV), a Flaviviridae pestivirus, is arguably one of the most widespread cattle pathogens worldwide. Each of its two genotypes has two biotypes, non-cytopathic (ncp) and cytopathic (cp). Only the ncp biotype of BVDV may establish persistent infection in the fetus when infecting a dam early in gestation, a time point which predates maturity of the adaptive immune system. Such fetuses may develop and be born healthy but remain infected for life. Due to this early initiation of fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 97 publications
1
97
0
5
Order By: Relevance
“…Bovine Viral Diarrhea Virus that includes two species, BVDV-1 and BVDV-2, is a member of Pestivirus genus within Flaviviridae virus family together with Border Disease Virus (BDV) and Classical Swine Fever Virus (CSFV) (9). BVDV mainly affects dairy and beef cattle which are considered as its natural hosts (8).…”
Section: Praca Oryginalnamentioning
confidence: 99%
See 2 more Smart Citations
“…Bovine Viral Diarrhea Virus that includes two species, BVDV-1 and BVDV-2, is a member of Pestivirus genus within Flaviviridae virus family together with Border Disease Virus (BDV) and Classical Swine Fever Virus (CSFV) (9). BVDV mainly affects dairy and beef cattle which are considered as its natural hosts (8).…”
Section: Praca Oryginalnamentioning
confidence: 99%
“…BVDV species have two well-known biotypes commonly described as cytopathic (cp) and non-cytopathic (ncp) according to their effects on cultured cells in vitro (9). Ncp biotypes are responsible for the vast majority of BVDV infection in living cattle at some stage of their lives (4,9).…”
Section: Praca Oryginalnamentioning
confidence: 99%
See 1 more Smart Citation
“…Pestivirus infection has only been recently recognized as a potential cause of serious illness in both NWCs and OWCs (Evermann, 2006), indicating that members of the camelid group are susceptible to infection. In NWCs, Pestivirus has been intensively researched in North America (Byers, 2008;Kim et al, 2009), the UK (Mueller and Broadbent, 2007) as well as in Switzerland (Danuser et al, 2009). BVDV may cause a severe disease in alpacas and llamas, including diarrhea, reproductive loss, wastage and death, posing a significant threat to a herd's health as it does in bovines (Belknap et al, 2000).…”
Section: Epidemiologymentioning
confidence: 99%
“…Mueller and Broadbent (2007) reported that the oldest surviving PI alpaca survived 30 months. In bovines, more than 50% of PI animals die before they reach the age of one year.…”
Section: Ajvmentioning
confidence: 99%